A case of renal vein branch injury identified by multidetector computed tomography. (February 2017) - Maruhashi, Takaaki; Kashimi, Fumie; Yamaya, Tatsuhiro; Takeuchi, Ichiro; Kataoka, Yuichi; Asari, Yasushi
Abstract: A 39-year-old male fell from a forklift and was urgently transported to our hospital. His vital signs were stable at the initial visit. Contrast imaging computed tomography (CT) showed extravasation (Ev) of contrast medium emigrating outside of the renal capsule and hematoma around the right kidney, and he was diagnosed with traumatic right renal injury, Grade IV laceration [American Association for the Surgery of Trauma classification]. When imaging the inferior renal artery branch extremity perfusing the area where Ev was found in the following blood vessel contrast imaging, obvious Ev was not found in the arterial phase; however, massively spreading Ev was found in the area adjacent to the renal laceration in the venous phase after taking a contrast image of the renal parenchyma. Thus, he was diagnosed with a renal vein branch injury. The transcatheter arterial embolization (TAE) was performed to the area, resulting in the disappearance of Ev. The effectiveness of TAE for renal injury has been established; however, it is only performed for arterial hemorrhage. TAE for venous injury has not previously been considered because a tamponade is supposedly effective for hemostasis of venous hemorrhage due to the anatomy surrounding Gerota's fasciae. This is an extremely rare case in which only venous injury was identified, without obvious arterial hemorrhage. Gerota's fasciae were broken and hemostasis treatment was required. Because the renal artery is the end artery, the venous hemorrhage was controlled with arterial embolization. In our case, renal vein branch injury was identified on CT and hemorrhage was terminated using TAE for the renal artery branch. TAE can be used as a non-operative management for the successful treatment of renal vein branch injury.